Penicillin Treatment Failure in Rabbit Syphilis Due to the Persistence of Treponemes (Treponema paraluisleporidarum Ecovar Cuniculus) in the Focus of Infection - Jekl, Vladimír; Nováková, Markéta; Jeklová, Edita; Pospíšilová, Petra; Křenová, Jitka; Faldyna, Martin; Škorič, Miša; Šmajs, David (Frontiers in Veterinary Science, 2021)
Rabbit venereal spirochetosis, a disease caused by Treponema paraluisleporidarum ecovar Cuniculus (TPeC), affects both wild and pet rabbits, and is transmitted sexually and via direct contact among animals. Treatment of syphilis in pet rabbits requires administration of antibiotics, including penicillin G, chloramphenicol, or fluoroquinolones. The aim of this work was to elucidate the cause of penicillin treatment failure in rabbit syphilis in a pet rabbit treated in Brno, Czech Republic, and to assess the phylogenetic relatedness of the agent to previously characterized pathogenic treponemes. Following amputation of the infected digits, the second round of penicillin treatment using the same dosage and application route resulted in the disappearance of clinical symptoms within a period of two weeks. The bacterium was successfully isolated from the claws, propagated in three experimental rabbits, and the resulting TPeC strain was designated as Cz-2020. Analysis of four genetic loci revealed that the Cz-2020 strain was similar but also clearly distinct from the only TPeC strain, which had been characterized in detail to date, i.e., the Cuniculi A strain, which was isolated in North America. The strain Cz-2020 represents the first available viable TPeC strain of European origin. DNA sequences encoding five penicillin-binding proteins of the strain Cz-2020 were compared to those of Cuniculi A, which is known to be sensitive to penicillin. The sequences differed in six nucleotides resulting in single amino acid changes in Penicillin-binding protein 1, 2 and 3. Since the second round of treatment was successful, we conclude that the penicillin treatment failure in the first round resulted from the presence of infection foci in claws where treponemes persisted.